Análise de ecoeficiência em um processo de moldagem plástica com adição de material reciclado em uma empresa do segmento automotivo - Domigos Filho, Jose (2013)
The purpose of this work is to verify the feasibility of using virgin material with addition of recycled material and analyze the level of ecoefficiency in a plastic molding area, in a company from the automotive segment. For this purpose, an exploratory research was conducted using a quantitative approach. Tests were conducted to confirm the thermal, physical and mechanical properties of the virgin material with addition of recycled material in comparison to 100% virgin material. Results indicated the technical feasibility of working with recycling rates of up to 20%. Four environmental indicators were used in the ecoefficiency analysis, considering nine injection molding machines. For the analysis of process ecoefficiency indicators for the 1st half of 2010, 2011 and 2012 were measured. Improvements showed a 13% increase between 2011 and 2012. With the results obtained, this study concludes that the proposals have been accepted of material with addition of recycled material, and the actions applied to the plastic molding process with their environmental aspects resulted in improved ecoefficiency, correlating results of production and environmental metrics for a proper measurement.